2021
DOI: 10.3390/brainsci11030366
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Child–Therapist Interaction in ASD Intervention: An Observational Coding System

Abstract: Background: Observational research plays an important part in developmental research due to its noninvasiveness. However, it has been hardly applied to investigate efficacy of the child–therapist interaction in the context of naturalistic developmental behavioral interventions (NDBI). In particular, the characteristics of child–therapist interplay are thought to have a significant impact in NDBIs in children with autism spectrum disorder (ASD). Quantitative approaches may help to identify the key features of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…We employed an observational coding system to quantitatively study the bidirectional interaction patterns displayed by the child and the clinician during the exchange ( 30 ). The coding schema consists of 15 codes that individuate both adult and child behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed an observational coding system to quantitatively study the bidirectional interaction patterns displayed by the child and the clinician during the exchange ( 30 ). The coding schema consists of 15 codes that individuate both adult and child behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…The Observational coding schema has previously shown a satisfactory construct validity. Further, two coders, experts in the field of autism spectrum disorder, were trained by a researcher to a reliability criterion of α > 0.80 and have previously shown satisfactory inter-rater reliability, measured with the Intraclass Correlation Coefficient (ICC) on the 20% of the videos independently coded ( n = 10) ( 30 ) (For further information, see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Not only do newborns largely depend on significant others in order to satisfy their fundamental needs, but the quality of early relational exchanges influence the infants' subsequent emotional, cognitive and social development (Belsky and Fearon, 2002 ; Malekpour, 2007 ; Groh et al, 2017 ; Bell, 2020 ; Cataldo et al, 2021 ). For this reason, studying the quality of early interactions has become the key to understanding typical and atypical trajectories that can emerge in the individual's development (Harrist and Waugh, 2002 ; Bertamini et al, 2021 ). Among others, synchrony proved useful in assessing relational quality (Leclère et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This technique may help harmonize the results of clinical trials and pool them in meta-analyses to better understand the actual efficacy of treatments for ASD. Finally, Bertamini et al [38] developed a novel observational coding system to quantify the child-therapist interaction in ASD intervention. The authors suggested that increased synchrony, successful strategies in engaging the children and longer and more complex interchanges, may be associated with favorable outcomes [38].…”
mentioning
confidence: 99%
“…Finally, Bertamini et al [38] developed a novel observational coding system to quantify the child-therapist interaction in ASD intervention. The authors suggested that increased synchrony, successful strategies in engaging the children and longer and more complex interchanges, may be associated with favorable outcomes [38].…”
mentioning
confidence: 99%